Farmers, Phantoms and Princes. The Canadian Pacific Railway and Filmmaking from 1899-1919 - Eamon, Greg (Cinémas, 1995)
The development of motion pictures coincided with the development of active publicity campaigns by the Canadian Pacific Railway Company. It did not take the CPR long to realize the potential of the new medium and capitalize on the public's fascination with train and motion. In order to encoutage immigration and settlement to western Canada, the company developed an extensive system of promotion which included the use of films. CPR filmmaking fell broadly into two categories, those which were designed with a specific intent to educate, inform and persuade and those which were primarily intended as entertainment. If CPR did not define the type of filmmaking rathet it facilitated the production of contemporary appeal.